DETECTING OF BOND DEFAULTS INDICATIONS USING FINANCIAL STATEMENT AND SHENANIGANS INDICATORS - Arya Wedha Rieantiari; Ancella Anitawati Hermawan (AFEBI Accounting Review, 2020)
This study aims to detect indications of bond defaults by conducting a thorough analysis of PT Trikomsel Oke, Tbk (TRIO)'s financial statements. TRIO's financial statements show that the company's revenue and profits increased during 2009-2014. However, the Indonesia rating agency (PEFINDO) declared default on the two bonds issued by TRIO in November 2015, even though the signal TRIO gave to its financial statements was an unqualified opinion from one of the big 4 Public Accountants for six consecutive years and PEFINDO's investment grade. This study uses a case study method.. Financial report data are analyzed by financial ratios and financial indicators of shenanigans. Evidence shows that there are indications of creative accounting and shenanigans before bonds were declared defaulted in 2015. With these results, this study suggests investors and creditors be more vigilant in analyzing published annual reports